INFLUENCE OF PLASTIC DEFORMATION PARAMETERS ON THE STRUCTURAL AND PHASE TRANSFORMATIONS IN DIFFERENT PURPOSES METALS - V. V. Chigirinskij; S. P. Shejko (Литьë и металлургия)
The influence of the parameters of controlled rolling on the structural phase transitions in low-alloy and carbon steels was analyzed.